Identification of ergonomic conditions in the service booths of a service company - Magno Ramos, Yahaira Celym (2024)
This study investigates the high absenteeism rate due to medical leave among toll collection agents in a toll company, leading to increased operational costs. The research identifies the workers' ergonomic conditions and primary musculoskeletal complaints, proposing a task redesign to reduce absenteeism caused by back, arm, and neck discomfort. Musculoskeletal discomfort across various body regions was measured using the Nordic questionnaire, while the RULA method assessed workers' exposure to ergonomic risks associated with their tasks. Findings reveal significant ergonomic hazards impacting worker health, consequently driving up operational expenses due to medical leave-related absenteeism. The study concludes with recommendations for task improvements, including posture corrections and enhancements to the ergonomic design of the toll collection agents' chairs.